(1-C5H14N2Br)2MnBr4: A Lead-Free Zero-Dimensional Organic-Metal Halide With Intense Green Photoluminescence - Jiang, Xiaomei; Chen, Zhaolai; Tao, Xutang (Frontiers in Chemistry, 2020)
Low-dimensional organic-inorganic hybrid materials have attracted tremendous attentions due to their fascinating properties as emerging star materials for light-emitting applications. Taking advantage of their rich chemical composition and structural diversity, here, a novel lead-free organic-manganese halide compound, (1-mPQBr)2MnBr4 (1-mPQ=1-methylpiperazine, 1-C5H14N2) with zero-dimensional structure has been rationally designed and successfully synthesized through solvent-evaporation method. Systematical characterizations were carried out to investigate the structure, thermal and photophysical properties. The (1-mPQBr)2MnBr4 was found to crystallized into an orthorhombic crystal (P212121) with lattice parameters of a=8.272(6) Å, b=15.982(10) Å and c=17.489(11) Å. The structure consists of isolated [MnBr4]2- clusters and free Br- ions as well as [C5H14N2]2+ molecules. Thermal analysis indicates that it is stable up to 300 °C. Upon ultraviolet photoexcitation, the (1-mPQBr)2MnBr4 exhibits intense green emission centered at 520 nm with a narrow full width at half-maximum of 43 nm at room temperature, which should be assigned to the spin-forbidden internal transition (4T1(G) to 6A1) of tetrahedrally coordinated Mn2+ ions. The superior photoluminescence properties coupled with facile and efficient synthesis method of this material suggest its considerable promise to be utilized as light-emitting materials.